Blood Pressure and Fibrinogen Responses to Mental Stress as Predictors of Incident Hypertension over an 8-Year Period. Issue 6 (11th July 2016) - Steptoe, Andrew; Kivimäki, Mika; Lowe, Gordon; Rumley, Ann; Hamer, Mark
Abstract: Background: Heightened blood pressure (BP) responses to mental stress predict raised BP levels over subsequent years, but evidence for associations with incident hypertension is limited, and the significance of inflammatory responses is uncertain. Purpose: We investigated the relationship between BP and plasma fibrinogen responses to stress and incident hypertension over an average 8-year follow-up. Method: Participants were 636 men and women (mean age 59.1 years) from the Whitehall II epidemiological cohort with no history of cardiovascular disease and hypertension. They performed standardized behavioral tasks (color/word conflict and mirror tracing), and hypertension was defined by clinic measures and medication status. Results: Of participants in the highest systolic BP reactivity tertile, 29.3 % became hypertensive over the follow-up period compared with 16.5 % of those in the lowest tertile, with an odds ratio of 2.02 (95 % CI 1.17–3.88, p = 0.012) after adjustment for age, sex, grade of employment, body mass index, smoking, alcohol consumption, physical activity, follow-up time, subjective stress response, perceived task difficulty, perceived task engagement, and baseline BP. Similar associations were observed for diastolic BP reactivity (odds ratio 2.05, 95 % CI 1.23–3.40, p = 0.006) and for impaired systolic BP post-stress recovery (odds ratio 2.06, 95 % CI 1.19–3.57, p = 0.010). Fibrinogen reactions to tasks also predicted future hypertension in women (odds ratio 2.64, 95 % CI 1.11–6.30, p = 0.029) but not men. Conclusions: These data suggest that heightened cardiovascular and inflammatory reactivity to mental stress is associated with hypertension risk, and may be a mechanism through which psychosocial factors impact on the development of hypertension.